MODEL SERVANT LEADERSHIP IN VILLAGE SERVICE (Study Case: Pemerintah Desa Randupitu, Gempol, Pasuruan) - Rozanatul Maroddah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The aim of this research is to investigate the implementation of servant leadership in the context of Randupitu Village, Gempol Pasuruan. The research subjects include the village head, hamlet head, and village officials. A descriptive qualitative approach with a multiple case study design was employed. Data collection procedures involved conducting interviews with relevant informants and consulting various sources such as government documents, video tapes, newspapers, letters, and books. The purpose was to gather information that could shed light on the question under study. Additionally, data analysis was carried out using the Grounded Theory - Strauss approach, which involved coding, including open coding, axial coding, and selective coding. The research analysis shows that the servant leadership model in the Randupitu Village Government has been successful in creating a supportive environment, paying attention to emotional well-being, developing the community's economy, providing real support, behaving ethically, empowering, and creating positive value for the entire village community.